Al-Qur’an Cetak di Indonesia Tinjauan Kronologis Pertengahan Abad ke-19 hingga Awal Abad ke-20 - Hakim, Abdul (SUHUF, 2012)
The mid-19th century towards the independence day of (1945) was a transition era of the production of the Qur'an in Indonesia. Started from the handwriting Qur’an, and was followed by lithography Qur’an, and the overseas Qur'anic publication, then the birth of the Qur'an which was produced by domestic production. This paper attempts to explain and analyze the development of the Qur'an in the colonial period, especially in the second half of the 19th century until the first half of the 20th century. This study explains the history of its publication, its validation by the committee, as well as aspects of the typographical arrangement and cover as well as the pattern of the text of the Qur'an being published at that time. The study also found some new data concerning the presence of the Qurans which is not mentioned in some of the existing writings.